MEDIA VIDEO UNTUK MENINGKATKAN PERILAKU PENGGUNAAN ANTIBIOTIKA UNTUK ANAK DENGAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) - Dian P. Sari; Yuni S. Arief; Ilya Krisnana (Universitas Airlangga, 2014)
Introduction: Acute Respiratory Infections (ARI), especially upper respiratory infections often affects 2-6 year-old children. It makes the mothers of the patients looking for a quick solution to cure ARI and ask the doctors to prescribe antibiotics and even buy them without any prescribtions. Video can be used to stimulate both auditory and visual system to change behavior. The aim of this study is to analyze effects of health education with the video as a media to change the behavior of mothers in the use of antibiotics in children with ARI.Method: This study used a pre-experimental design. Its population is mothers who have children with a history of ARI that is in the Public Health of Mulyorejo. The sample is chosen through purposive sampling technique. The independent variable is health education with video as a media, while the dependent variable is the knowledge and attitude of mothers. Data were collected by questionnaire that has been test for validity and reliability and analyzed using Wilcoxon Signed Rank Test with alpha level ≤ 0.05.Results: This study showed result that this method affects the change in knowledge (p=0.000) but the attitude has not changed with p = 0.414.Conclusion: It can be concluded that health education with video as a media can be used by healthcare providers to improve knowledge of mothers in the use of antibiotics in children with ARI. Future studies are expected to be carried out more samples and add the intensity in giving of this method to increase the mother’s attitude.